The risk of death associated with proteinuria in heart failure is restricted to patients with an elevated blood urea nitrogen to creatinine ratio. (15th July 2016) - Brisco, Meredith A.; Zile, Michael R.; ter Maaten, Jozine M.; Hanberg, Jennifer S.; Wilson, F. Perry; Parikh, Chirag; Testani, Jeffrey M.
Abstract: Background: Renal dysfunction (RD) is associated with reduced survival in HF; however, not all RD is mechanistically or prognostically equivalent. Notably, RD associated with "pre-renal" physiology, as identified by an elevated blood urea nitrogen to creatinine ratio (BUN/Cr), identifies a particularly high risk RD phenotype. Proteinuria, another domain of renal dysfunction, has also been associated with adverse events. Given that several different mechanisms can cause proteinuria, we sought to investigate whether the mechanism underlying proteinuria also affects survival in HF. Methods and Results: Subjects in the Studies of Left Ventricular Dysfunction (SOLVD) trial with proteinuria assessed at baseline were studied ( n  = 6439). All survival models were adjusted for baseline characteristics and estimated glomerular filtration rate (eGFR). Proteinuria (trace or 1 +) was present in 26% and associated with increased mortality (HR = 1.2; 95% CI, 1.1–1.3, p  = 0.006). Proteinuria > 1 + was less common (2.5%) but demonstrated a stronger relationship with mortality (HR = 1.9; 95% CI, 1.5–2.5, p  < 0.001). In patients with BUN/Cr in the top tertile (≥ 17.3), any proteinuria (HR = 1.3; 95% CI, 1.1–1.5, p  = 0.008) and > 1 + proteinuria (HR = 2.3; 95% CI, 1.7–3.3, p  < 0.001) both remained associated with mortality. However, in patients with BUN/Cr in the bottom tertile (≤ 13.3), any proteinuria (HR = 0.95; 95% CI, 0.77–1.2, p  = 0.63, p interaction = 0.015) and > 1 + proteinuria (HR = 1.3; 95% CI, 0.79–2.2, p  = 0.29, p interaction = 0.036) were not associated with worsened survival. Conclusion: Analogous to a reduced eGFR, the mechanism underlying proteinuria in HF may be important in determining the associated survival disadvantage.